The primary importance of corporate social responsibility and ethicality in corporation reputation: an empirical study - Walker, Kent; Dyck, Bruno (Business and Society Review, 2014)
We examine three assumptions commonly held in the corporate reputation literature: i) reputation ratings of owners and investors are generally representative of all stakeholders; ii) stakeholders will generally provide a higher reputation rating to firms that emphasize corporate social responsibility versus firms that do not; and iii) profitability is the primary criterion of importance to all stakeholders when rating a firm’s reputation. Using an exploratory in-class exercise our findings suggest that: i) there are significant differences among stakeholder groups in their reputation ratings; ii) firms that emphasize corporate social responsibility are not rated more highly across all stakeholder groups, and iii) for all stakeholder groups, the ethicality criterion explained more of the variance in firms’ reputation ratings than the profitability criterion.
Keywords: CSR; Corporate Reputation; Corporate Social Responsibility; Criteria; Ethics; Profitability; RSE; Stakeholders

Corporate Social Responsibility (CSR) in the OHADA Law - Diawara, Karounga; Lavallée, Sophie (Journal of Business Law and Ethics, 2014)
CSR refers primarily to a framework idea according to which a corporation is encouraged, if not obliged, to go beyond the speculative and economic goals that benefit its members only, in order to integrate, into its decision-making process, other more holistic considerations of an ethical, social and environmental nature for the benefit of all stakeholders. CSR is a key concept that attempts to reconcile economic objectives with social, ethical and environmental considerations, with the particularity of questioning interactions between a corporation and its societal, ethical and ecological environment. This paper has a modest, but not uninteresting, objective. First, it offers an exploratory study that sets out markers for a more exhaustive analysis of the potential for CSR in the field of law in the Ohada zone. Our study is intended to be both theoretical and pragmatic: it asks questions and suggests topics for review from a normative standpoint largely inspired by socio-economic analysis. One of the interesting features of our approach is to consider, comprehensively, a complex notion that reflects several different concerns and is crossed by various conceptual frameworks that must be re-read in an “enlightened” manner, to see how it could potentially be made operational as part of Ohada law. This previously unexplored approach could lead, in time, to the establishment of a transnational committee on CSR in the Ohada zone.
Keywords: CSR; RSE